Development of the Jepara Culture Encyclopedia (EDIBARA) to Improve Understanding of Cultural Concepts In Elementary School Students - Fadia Risqi Dwiyanti; Muh Muhaimin (Jurnal Kiprah Pendidikan, 2026)
Learning local culture in elementary schools still faces challenges, particularly the limited availability of engaging and interactive learning media, which results in suboptimal student understanding of cultural concepts. Therefore, learning media are needed to help students understand local culture in a more engaging and accessible way. This study aims to develop and examine the feasibility and effectiveness of the Jepara Cultural Interactive Digital Encyclopedia (EDIBARA) as a learning media for elementary school students. This study employed a Research and Development (R&D) method using the ADDIE model. The subjects included media experts, material experts, and 20 fourth-grade students. The instruments consisted of validation questionnaires and pre-test and post-test assessments. Data were analyzed using percentage techniques and the N-Gain Score. The results showed a feasibility level of 83.11% (very feasible) and an N-Gain score of 0.379 (moderate category), indicating an improvement in students’ understanding. Therefore, EDIBARA has the potential to be used as a learning media, although its effectiveness still requires further optimization